Exacerbation of pulmonary cryptococcosis associated with enhancement of Th2 response in the postpartum period. Issue 8 (August 2021) - Miyoshi, Shota; Oda, Naohiro; Gion, Yuka; Taki, Takahiro; Mitani, Reo; Takata, Ichiro; Taniguchi, Akihiko; Sato, Yasuharu; Miyahara, Nobuaki
Abstract: Cryptococcosis is an invasive mycosis that has become increasingly prevalent in immunocompromised patients. Pregnant women are also one of the risk populations for cryptococcosis. Reversal of Th2 to Th1 response following resolution of immunosuppression during the postpartum period can lead to overt clinical manifestations of a previously silent infection, resembling an immune reconstitution inflammatory syndrome. Here, we report a case of a 30-year-old woman who had an exacerbation of pulmonary cryptococcosis in the postpartum period mimicking an immune reconstitution inflammatory syndrome. In the present case, chest computed tomography showed multiple small nodules on the day of the delivery; however, pulmonary cryptococcosis, which was subclinical during pregnancy, rapidly worsened to mass-like consolidation at one month after the delivery. Pathohistological examination of the lung specimen showed lung parenchyma infiltration with histiocytes and numerous lymphocytes without granulomatous formations, and a small number of yeast-like organisms consistent with Cryptococcus without capillary involvement. Immunohistochemical staining showed predominance of CD3 + cells and CD4 + cells over CD8 + cells. In addition, GATA3+ cells dominated over T-bet + cells. These data suggested exacerbation of pulmonary cryptococcosis associated with enhancement of Th2 response in the postpartum period.